2017
DOI: 10.1111/gcb.13750
|View full text |Cite
|
Sign up to set email alerts
|

Higher climate warming sensitivity of Siberian larch in small than large forest islands in the fragmented Mongolian forest steppe

Abstract: Forest fragmentation has been found to affect biodiversity and ecosystem functioning in multiple ways. We asked whether forest size and isolation in fragmented woodlands influences the climate warming sensitivity of tree growth in the southern boreal forest of the Mongolian Larix sibirica forest steppe, a naturally fragmented woodland embedded in grassland, which is highly affected by warming, drought, and increasing anthropogenic forest destruction in recent time. We examined the influence of stand size and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
(87 reference statements)
2
30
2
1
Order By: Relevance
“…In addition, a lack of shrub recruitment was also observed in response to abnormal warming during recent years in polar dry biomes (Boulanger-Lapointe et al 2014, B€ untgen et al 2015. In several drought-prone treeline sites worldwide, low tree recruitment has also been observed in recent decades (Cuevas 2002, Camarero and Guti errez 2004, Dulamsuren et al 2010, Khansaritoreh et al 2017, Xu et al 2017. Drought stress may be even more intense at shrublines, where rocky and shallow sandy soils amplify evaporation and soil moisture loss under warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lack of shrub recruitment was also observed in response to abnormal warming during recent years in polar dry biomes (Boulanger-Lapointe et al 2014, B€ untgen et al 2015. In several drought-prone treeline sites worldwide, low tree recruitment has also been observed in recent decades (Cuevas 2002, Camarero and Guti errez 2004, Dulamsuren et al 2010, Khansaritoreh et al 2017, Xu et al 2017. Drought stress may be even more intense at shrublines, where rocky and shallow sandy soils amplify evaporation and soil moisture loss under warming climate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these relationships they projected better future forest conditions for Mongolia until 2100. In opposition to these findings, Bayartaa et al (2007) reported that climate scenarios would indicate a significant decrease in forest area and its total biomass for Mongolia until the middle of the 21st Century, which is in accordance with the recent trends from dendrochronological data from Mongolia (Dulamsuren et al, 2010a(Dulamsuren et al, , b, 2014Khansaritoreh et al, 2017). Lu et al (2014) investigated the applicability of different remote sensing-based biomass estimation approaches.…”
Section: Introductionmentioning
confidence: 94%
“…Elevation of the selected stands varied between 1809 and 2135 m a.s.l. The distance of the sampled trees to the lower forest line was between 110 and 330 m. Forests of the different size classes were characterized by differences in microclimate and land use intensity (Khansaritoreh et al 2017). Individual forest stands from different size classes were selected randomly based on remote-sensing analysis of forest distribution in the study region.…”
Section: Study Design and Core Samplingmentioning
confidence: 99%
“…Studying the annual stem increment of L. sibirica in forest stands of different size, Khansaritoreh et al (2017) found that the sensitivity of stemwood production to summer drought increased with decreasing stand size, because maximum air temperatures increased and relative humidity decreased with decreasing stand size. This means that anthropogenic forest fragmentation exacerbates the detrimental impact of global warming on tree growth in a region, which is exposed to temperature increases far above the global average (IPCC 2013) and where L. sibirica widely shows growth depressions, failure of regeneration, and increased mortality (Dulamsuren et al 2010;Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%